Trade Liberalization, Exchange Rate Changes, and Tax Revenue in Sub-Saharan Africa - Agbeyegbe, Terence (IMF Working Papers; Working Paper, 2004)
Empirical evidence on the relationship between trade liberalization, exchange rates, and tax revenue is mixed. This paper examines these linkages anew. Using a panel of 22 countries in Sub-Saharan Africa, over 1980-1996, we perform Generalized Method of Moment regressions to test this relationship. We find evidence that the relationship between trade liberalization and tax revenue is sensitive to the measure used to proxy trade liberalization, but that, in general, trade liberalization is not strongly linked to aggregate tax revenue or its components-though with one measure, it is linked to higher income tax revenue. Currency appreciation and higher inflation show some linkage to lower tax revenues or its components. These results show some partial consistency with previous findings, and support the notion that trade liberalization accompanied by appropriate macroeconomic policies can be undertaken in a way that preserves overall revenue yield.